Analysis of pesticides in food and environmental samples by enzyme-linked immunosorbent assays - Nunes, G. S.; Toscano, I. A.; Barcelo, D. (Elsevier B.V., 1998)
Enzyme-linked immunosorbent assays (ELISAs) are the most extensively studied types of immunoassay and their application in pesticide residue monitoring is an area with enormous potential for growth. In comparison with classical analytical methods, ELISA methods offer the possibility of highly sensitive, relatively rapid, and cost-effective measurements. This review introduces the general ELISA formats used, focusing on their use in pesticide analysis. Identifying and studying the effects of interferences in immunoassays is an active area of research and we discuss the matrix effects observed in several studies involving e.g. food, crop and environmental samples. The procedures to eliminate the matrix interferences are briefly discussed. (C) 1998 Elsevier B.V. B.V.
Keywords: enzyme-linked immunosorbent assay; pesticide residue; food; crop; environmental sample; matrix effect